Preparation method of water-based zinc ion battery positive electrode material with nuclear ring confinement structure

By synthesizing vanadium disulfide in situ in mesoporous carbon nanospheres to form a nuclear ring boundary structure, the problem of vanadium-based material VS2 easily damaged during charging and discharging is solved, and the rate performance and cycle stability of aqueous zinc ion batteries are improved. , extends battery life.

CN119191261APending Publication Date: 2024-12-27YANCHENG TEACHERS UNIV

Patent Information

Application Number
CN202411296394.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing vanadium-based material VS2 water-based zinc-ion battery is easily damaged when it is repeatedly charged and discharged, resulting in the shortening of battery life and poor circulation performance.

Method used

采用水热合成法制备核环限域结构水系锌离子电池正极材料,通过在介孔碳纳米球中原位合成二硫化钒,形成三维纳米空心介孔碳纳米球,提高导电性和机械稳定性,防止二硫化钒在充放电过程中的结构脱落。

Benefits of technology

It improves the rate performance and cycle stability of the material, extends the battery life, enhances the transportation efficiency of zinc ions and electrons, reduces structural collapse, and improves the mechanical stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191261A_ABST
    Figure CN119191261A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of nano material production, in particular to a preparation method of a core-ring confinement structure aqueous zinc ion battery positive electrode material, which comprises the following steps: by taking resorcinol and formaldehyde as carbon sources and tetraethoxysilane as a silicon source, forming hollow mesoporous carbon nanospheres by magnetic stirring, calcining and etching methods; and obtaining the water-based zinc ion battery positive electrode material with the nuclear ring confinement structure through vacuum degassing and a hydrothermal method. Wherein the three-dimensional nano hollow mesoporous carbon nanospheres show very high specific surface area, uniform porosity and good conductivity, and are beneficial to rapid transportation of zinc ions and electrons; the core-ring structure VS2 in the carbon sphere can prevent the structure from falling off in the charge-discharge process, the internal space can buffer the volume effect in the embedding / dezincification process, and the stability of the structure in the cycle process is facilitated, so that the material has good rate capability and cycle stability, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano material production, and in particular to a method for preparing a core-ring confined structure aqueous zinc ion battery positive electrode material. Background Art

[0002] Vanadium-based materials are a very good class of aqueous zinc-ion battery materials. In addition to manganese-based compounds, vanadium-based compounds have become a very promising positive electrode material for aqueous zinc-ion batteries due to their large theoretical capacity, a wide variety of crystal structures, abundant resources, and low cost, especially in zinc-ion batteries. Among them, the vanadium-based material VS2, the vanadium layer is located between the two sulfur layers, forming a SVS sandwich structure with an interlayer spacing of It is suitable for lithium / sodium and zinc ion shuttling, and its inherent metallic conductivity has greater advantages than other vanadium-based materials with poor conductivity.

[0003] In the prior art, some vanadium-based VS2 aqueous zinc-ion battery materials do not consider the problem that the VS2 structure is easily destroyed during repeated charging and discharging, which shortens the battery life. For example, patent technology document CN115092960A discloses a defect-rich vanadium disulfide and its preparation method and its application as a positive electrode material in an aqueous zinc-ion battery. The preparation process of the defect-rich layered transition metal disulfide VS2 powder material includes a one-step hydrothermal method and subsequent in-situ electrochemical activation under high pressure, and the obtained VS2 has a relatively unique structure. The preparation process of the invention is simple and when VS2 is used as a positive electrode material for an aqueous zinc-ion battery, it exhibits extremely high specific capacity and excellent rate performance. However, since the single-component vanadium disulfide is a layered structure, the embedding of zinc ions will cause changes in volume or structure, and the battery reuse rate is poor.

[0004] Patent document CN108597908A discloses a three-dimensional porous graphene-vanadium disulfide composite electrode material, its preparation method and its application, wherein the composite electrode material comprises porous graphene oxide and vanadium disulfide coated with the porous graphene oxide. In the invention, porous graphene oxide can improve the conductivity of vanadium disulfide and inhibit the volume expansion and phase change of vanadium disulfide during the charging and discharging process, but the production cost of graphene material is relatively high, and it is easy to oxidize and degrade under high temperature and high humidity environment, and its stability needs to be improved, and it lacks practicality.

[0005] Therefore, according to the above-mentioned related technologies, it is urgent to develop a core-ring confined structure aqueous zinc ion battery positive electrode material with good rate performance, not easily destroyed structure and stable cycle performance. Summary of the invention

[0006] In view of this, the purpose of the present invention is to propose a method for preparing a core-ring confined structure aqueous zinc ion battery positive electrode material to solve the problems of poor rate performance, destruction of VS2 structure during charge and discharge, and unstable cycle in the prior art.

[0007] Based on the above purpose, the present invention provides a method for preparing a core-ring confined structure aqueous zinc ion battery positive electrode material.

[0008] A method for preparing a core-ring confined structure aqueous zinc ion battery positive electrode material comprises the following steps:

[0009] Step S1. Add deionized water, anhydrous ethanol and ammonia water into a beaker and stir evenly to obtain a mixture A; then add ethyl orthosilicate, resorcinol and formaldehyde solution into the mixture A in sequence and stir to obtain a mixture B;

[0010] Step S2. Wash the mixture B by centrifugation, obtain the solid phase and dry it to obtain compound C; calcine compound C at high temperature under nitrogen atmosphere protection, and etch it with a strong alkaline solution in a water bath to obtain compound D;

[0011] Step S3. Centrifugally washing and drying the compound D to obtain hollow mesoporous carbon nanospheres;

[0012] Step S4. dissolving ammonium metavanadate in deionized water, adding ammonia water, and ultrasonically forming a transparent solution E; ultrasonically dispersing thioacetamide and hollow mesoporous carbon nanospheres in solution E, degassing under vacuum conditions, hydrothermal reaction, centrifugal washing, obtaining a solid phase, and vacuum drying to obtain modified mesoporous carbon nanospheres A;

[0013] Step S5. dissolving ammonium metavanadate in deionized water, adding ammonia water, and ultrasonically forming a transparent solution E; ultrasonically dispersing thioacetamide and hollow mesoporous carbon nanospheres in solution E, degassing under vacuum conditions, hydrothermal reaction, centrifugal washing, obtaining a solid phase, and vacuum drying to obtain modified mesoporous carbon nanospheres B;

[0014] Step S6. Mixing the modified mesoporous carbon nanosphere A and the modified mesoporous carbon nanosphere B to obtain a core-ring confined structure aqueous zinc ion battery positive electrode material;

[0015] The diameter of the hollow mesoporous carbon nanospheres in step S4 is 200-300 nm;

[0016] The diameter of the hollow mesoporous carbon nanospheres in step S5 is 600-800 nm;

[0017] The mass ratio of the modified mesoporous carbon nanospheres A and the modified mesoporous carbon nanospheres B mixed in step S6 is 7:3.

[0018] Preferably, the volume ratio of deionized water, anhydrous ethanol and ammonia water in step S1 is 3-8:23-47:1.

[0019] Preferably, the mass fraction of the ammonia water in step S1 is 25%.

[0020] Preferably, in step S1, the mass ratio of ethyl orthosilicate, resorcinol and formaldehyde is 0.2-0.8:0.1-0.5:0.1-1, and the stirring time is 20-24 hours.

[0021] Preferably, in step S2, the high temperature calcination temperature is 500-700°C, the heating rate is 1-5°C / min, and the water bath temperature is 70°C.

[0022] Preferably, the strong alkali solution in step S2 is sodium hydroxide or potassium hydroxide, and the concentration of the strong alkali solution is 1-3 mol / L.

[0023] Preferably, in step S2, the etching temperature is 70° C., and the etching time is 16-20 hours.

[0024] Preferably, the carbon wall thickness of the hollow mesoporous carbon nanospheres in step S3 is 8-10 nm, and the mesopore size is 1-5 nm.

[0025] Preferably, in step S4, the mass ratio of ammonium metavanadate, thioacetamide and hollow mesoporous carbon nanospheres is 0.3-0.8:0.3-2:0.03-0.1, and the volume ratio of ammonia water to deionized water is 1-4:10-30;

[0026] In step S5, the mass ratio of ammonium metavanadate, thioacetamide and hollow mesoporous carbon nanospheres is 0.3-0.8:0.3-2:0.03-0.1, and the volume ratio of ammonia water to deionized water is 1-4:10-30.

[0027] Preferably, the vacuum degassing equipment in step S4 is a circulating water vacuum pump with a vacuum degree of -0.1--0.07MPa;

[0028] The hydrothermal reaction temperature in step S4 is 100-200° C., and the reaction time is 8-12 h.

[0029] Beneficial effects of the present invention:

[0030] The invention provides a method for preparing a core-ring confined structure aqueous zinc ion battery positive electrode material. The invention prepares a core-ring structure of in-situ synthesized vanadium disulfide inside mesoporous carbon nanospheres A and mesoporous carbon nanospheres B with different particle sizes by a hydrothermal synthesis method, and then mixes the modified mesoporous carbon nanospheres A and the modified mesoporous carbon nanospheres B to obtain a core-ring confined structure aqueous zinc ion battery positive electrode material, wherein the three-dimensional nano hollow mesoporous carbon nanospheres have a high specific surface area and a high porosity, which is conducive to the rapid transportation of zinc ions and electrons, thereby improving the conductivity of the composite material; the mesoporous carbon nanospheres with different particle sizes can more effectively disperse and load active components, improve the loading efficiency and prevent the aggregation of active components, while reducing the structural collapse during use and improving the mechanical stability of the material;

[0031] The core-ring structure provided in the present invention can prevent the vanadium disulfide from falling off during the charge and discharge process, and the modified mesoporous carbon nanospheres A and B can also buffer the volume effect during the zinc insertion / extraction process, which is beneficial to the stability of the structure during the cycle process, so that the material has good rate performance and cycle stability, so that the active material is effectively protected in large current and long cycle. Compared with the existing technology, it has a wide range of application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 They are TEM images of hollow mesoporous carbon nanospheres prepared in the present invention at different magnifications;

[0034] Figure 2 They are TEM images of the modified mesoporous carbon nanospheres A prepared in the present invention at different magnifications;

[0035] Figure 3 This is a charge-discharge cycle performance diagram of the modified mesoporous carbon nanosphere A prepared in the present invention at a rate of 1A / g;

[0036] Figure 4 This is a rate performance diagram of the modified mesoporous carbon nanospheres A prepared in the present invention. DETAILED DESCRIPTION

[0037] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0038] The sources and properties of some of the raw materials used in the present invention are as follows:

[0039] Anhydrous ethanol was purchased from Shandong Xuchen Chemical Technology Co., Ltd.; deionized water was purchased from Shanghai Jizhou Chemical Technology Co., Ltd.; ammonia water was purchased from Jinan Haicheng Chemical Co., Ltd.; tetraethyl orthosilicate was purchased from Wuhan Jiyesheng Chemical Co., Ltd.; resorcinol was purchased from Hebei Yanxi Chemical Co., Ltd.; formaldehyde was purchased from Wuhan Xinyuhang Chemical Co., Ltd.; sodium hydroxide was purchased from Shanghai Zeye Biotechnology Co., Ltd.; ammonium metavanadate was purchased from Wuhan Kmik Biomedical Technology Co., Ltd.; and thioacetamide was purchased from Shandong Suitai Biotechnology Co., Ltd.

[0040] Embodiment 1: A method for preparing a core-ring confined structure aqueous zinc ion battery positive electrode material, comprising the following steps:

[0041] Step S1. Add 3 mL of deionized water, 23 mL of anhydrous ethanol, and 1 mL of aqueous ammonia into a beaker and stir evenly to obtain a mixture A; then add 0.2 g of ethyl orthosilicate, 0.1 g of resorcinol, and 0.1 g of formaldehyde solution to the mixture A in sequence and stir for 20 h to obtain a mixture B;

[0042] Step S2. The mixture B is centrifuged and washed, and the solid phase is obtained and then dried to obtain a compound C; the compound C is calcined at 500° C. for 30 h under a nitrogen atmosphere, with a heating rate of 1° C. / min, and etched with a 1 mol / L sodium hydroxide solution in a 70° C. water bath for 16 h to obtain a compound D;

[0043] Step S3. Centrifugally washing and drying the compound D to obtain hollow mesoporous carbon nanospheres;

[0044] Step S4. 0.3 g of ammonium metavanadate was dissolved in 10 mL of deionized water, 1 mL of ammonia water was added, and ultrasonic dispersion was performed to form a transparent solution E; 0.3 g of thioacetamide and 0.03 g of hollow mesoporous carbon nanospheres with a diameter of 200-300 nm were ultrasonically dispersed in solution E, and degassed using a circulating water vacuum pump with a vacuum degree of -0.07 MPa, and then the black solution was transferred to a 50 mL stainless steel autoclave; the solution was hydrothermally reacted at 100 ° C in a blast drying oven for 8 h, and after the reaction was completed, the solution was centrifuged and washed, washed with deionized water and ethanol for 6 times, and then vacuum dried at 60 ° C for 8 hours to obtain modified mesoporous carbon nanospheres A;

[0045] Step S5. 0.3 g of ammonium metavanadate was dissolved in 10 mL of deionized water, 1 mL of ammonia water was added, and ultrasonic dispersion was performed to form a transparent solution E; 0.3 g of thioacetamide and 0.03 g of hollow mesoporous carbon nanospheres with a diameter of 600-800 nm were ultrasonically dispersed in solution E, and degassed using a circulating water vacuum pump with a vacuum degree of -0.07 MPa, and then the black solution was transferred to a 50 mL stainless steel autoclave; the solution was hydrothermally reacted at 100 ° C in a blast drying oven for 8 h, and after the reaction was completed, the solution was centrifuged and washed, washed with deionized water and ethanol for 6 times, and then vacuum dried at 60 ° C for 8 hours to obtain modified mesoporous carbon nanospheres B;

[0046] Step S6. The modified mesoporous carbon nanospheres A and the modified mesoporous carbon nanospheres B are mixed in a mass ratio of 7:3 to obtain a core-ring confined structure aqueous zinc ion battery positive electrode material.

[0047] Embodiment 2: A method for preparing a core-ring confined structure aqueous zinc ion battery positive electrode material, comprising the following steps:

[0048] Step S1. Add 5 mL of deionized water, 32 mL of anhydrous ethanol, and 1 mL of aqueous ammonia into a beaker and stir evenly to obtain a mixture A; then add 0.4 g of ethyl orthosilicate, 0.2 g of resorcinol, and 0.4 g of formaldehyde solution to the mixture A in sequence and stir for 21 hours to obtain a mixture B;

[0049] Step S2. The mixture B is centrifuged and washed, and the solid phase is obtained and then dried to obtain a compound C; the compound C is calcined at 600° C. for 28 h under a nitrogen atmosphere, with a heating rate of 2° C. / min, and etched with a 1.5 mol / L sodium hydroxide solution in a 70° C. water bath for 17 h to obtain a compound D;

[0050] Step S3. Centrifugally washing and drying the compound D to obtain hollow mesoporous carbon nanospheres;

[0051] Step S4. 0.5 g of ammonium metavanadate was dissolved in 15 mL of deionized water, 2 mL of ammonia water was added, and ultrasonic dispersion was performed to form a transparent solution E; 0.9 g of thioacetamide and 0.05 g of hollow mesoporous carbon nanospheres with a diameter of 200-300 nm were ultrasonically dispersed in solution E, and degassed using a circulating water vacuum pump with a vacuum degree of -0.08 MPa, and then the black solution was transferred to a 50 mL stainless steel autoclave; the solution was hydrothermally reacted at 150° C. in a blast drying oven for 9 h, and after the reaction was completed, the solution was centrifuged and washed, washed with deionized water and ethanol for 6 times, and then vacuum dried at 60° C. for 8 hours to obtain modified mesoporous carbon nanospheres A;

[0052] Step S5. 0.5 g of ammonium metavanadate was dissolved in 15 mL of deionized water, 2 mL of ammonia water was added, and ultrasonic dispersion was performed to form a transparent solution E; 0.9 g of thioacetamide and 0.05 g of hollow mesoporous carbon nanospheres with a diameter of 600-800 nm were ultrasonically dispersed in solution E, and degassed using a circulating water vacuum pump with a vacuum degree of -0.08 MPa, and then the black solution was transferred to a 50 mL stainless steel autoclave; the solution was hydrothermally reacted at 150° C. in a blast drying oven for 9 h, and after the reaction was completed, the solution was centrifuged and washed, washed with deionized water and ethanol for 6 times, and then vacuum dried at 60° C. for 8 hours to obtain modified mesoporous carbon nanospheres B;

[0053] Step S6. The modified mesoporous carbon nanospheres A and the modified mesoporous carbon nanospheres B are mixed in a mass ratio of 7:3 to obtain a core-ring confined structure aqueous zinc ion battery positive electrode material.

[0054] Embodiment 3: A method for preparing a core-ring confined structure aqueous zinc ion battery positive electrode material, comprising the following steps:

[0055] Step S1. Add 7 mL of deionized water, 40 mL of anhydrous ethanol, and 1 mL of aqueous ammonia into a beaker and stir evenly to obtain a mixture A; then add 0.6 g of ethyl orthosilicate, 0.4 g of resorcinol, and 0.7 g of formaldehyde solution into the mixture A in sequence and stir for 23 h to obtain a mixture B;

[0056] Step S2. The mixture B is centrifuged and washed, and the solid phase is obtained and then dried to obtain a compound C; the compound C is calcined at 650° C. for 26 h under a nitrogen atmosphere with a heating rate of 4° C. / min and etched with a 2 mol / L sodium hydroxide solution for 19 h in a 70° C. water bath to obtain a compound D;

[0057] Step S3. Centrifugally washing and drying the compound D to obtain hollow mesoporous carbon nanospheres;

[0058] Step S4. 0.7 g of ammonium metavanadate was dissolved in 20 mL of deionized water, 3 mL of ammonia water was added, and ultrasonic dispersion was performed to form a transparent solution E; 1.5 g of thioacetamide and 0.07 g of hollow mesoporous carbon nanospheres with a diameter of 200-300 nm were ultrasonically dispersed in solution E, and degassed using a circulating water vacuum pump with a vacuum degree of -0.09 MPa, and then the black solution was transferred to a 50 mL stainless steel autoclave; the solution was hydrothermally reacted at 175 ° C in a blast drying oven for 11 h, and after the reaction was completed, the solution was centrifuged and washed, washed with deionized water and ethanol for 6 times, and then vacuum dried at 60 ° C for 8 hours to obtain modified mesoporous carbon nanospheres A;

[0059] Step S5. 0.7 g of ammonium metavanadate was dissolved in 20 mL of deionized water, 3 mL of ammonia water was added, and ultrasonic dispersion was performed to form a transparent solution E; 1.5 g of thioacetamide and 0.07 g of hollow mesoporous carbon nanospheres with a diameter of 600-800 nm were ultrasonically dispersed in solution E, and degassed using a circulating water vacuum pump with a vacuum degree of -0.09 MPa, and then the black solution was transferred to a 50 mL stainless steel autoclave; the solution was hydrothermally reacted at 175° C. in a blast drying oven for 11 h, and after the reaction was completed, the solution was centrifuged and washed, washed with deionized water and ethanol for 6 times, and then vacuum dried at 60° C. for 8 hours to obtain modified mesoporous carbon nanospheres B;

[0060] Step S6. The modified mesoporous carbon nanospheres A and the modified mesoporous carbon nanospheres B are mixed in a mass ratio of 7:3 to obtain a core-ring confined structure aqueous zinc ion battery positive electrode material.

[0061] Example 4: A method for preparing a core-ring confined structure aqueous zinc ion battery positive electrode material, comprising the following steps:

[0062] Step S1. Add 8 mL of deionized water, 47 mL of anhydrous ethanol, and 1 mL of aqueous ammonia into a beaker and stir evenly to obtain a mixture A; then add 0.8 g of ethyl orthosilicate, 0.5 g of resorcinol, and 1 g of formaldehyde solution to the mixture A in sequence and stir for 24 h to obtain a mixture B;

[0063] Step S2. The mixture B is centrifuged and washed, and the solid phase is obtained and then dried to obtain a compound C; the compound C is calcined at 700° C. for 24 h under a nitrogen atmosphere, with a heating rate of 5° C. / min, and etched with a 3 mol / L sodium hydroxide solution in a 70° C. water bath for 20 h to obtain a compound D;

[0064] Step S3. Centrifugally washing and drying the compound D to obtain hollow mesoporous carbon nanospheres;

[0065] Step S4. 0.8 g of ammonium metavanadate was dissolved in 30 mL of deionized water, 4 mL of ammonia water was added, and ultrasonic dispersion was performed to form a transparent solution E; 2 g of thioacetamide and 1 g of hollow mesoporous carbon nanospheres with a diameter of 200-300 nm were ultrasonically dispersed in solution E, and degassed using a circulating water vacuum pump with a vacuum degree of -0.1 MPa, and then the black solution was transferred to a 50 mL stainless steel autoclave; the solution was hydrothermally reacted at 200 ° C in a blast drying oven for 12 h, and after the reaction was completed, the solution was centrifuged and washed, washed with deionized water and ethanol for 6 times, and then vacuum dried at 60 ° C for 8 hours to obtain modified mesoporous carbon nanospheres A;

[0066] Step S5. 0.8 g of ammonium metavanadate was dissolved in 30 mL of deionized water, 4 mL of ammonia water was added, and ultrasonic dispersion was performed to form a transparent solution E; 2 g of thioacetamide and 1 g of hollow mesoporous carbon nanospheres with a diameter of 600-800 nm were ultrasonically dispersed in solution E, and degassed using a circulating water vacuum pump with a vacuum degree of -0.1 MPa, and then the black solution was transferred to a 50 mL stainless steel high-pressure reactor; hydrothermal reaction was performed at 200° C. in a blast drying oven for 12 h, and after the reaction was completed, the solution was centrifuged and washed, washed with deionized water and ethanol for 6 times, and then vacuum dried at 60° C. for 8 hours to obtain modified mesoporous carbon nanospheres B;

[0067] Step S6. The modified mesoporous carbon nanospheres A and the modified mesoporous carbon nanospheres B are mixed in a mass ratio of 7:3 to obtain a core-ring confined structure aqueous zinc ion battery positive electrode material.

[0068] Comparative Example 1:

[0069] Compared with Example 1, this comparative example does not add 70% of modified mesoporous carbon nanospheres A, and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, a core-ring confined structure aqueous zinc ion battery positive electrode material is obtained.

[0070] Comparative Example 2:

[0071] Compared with Example 1, this comparative example only adjusts the "modified mesoporous carbon nanospheres A and modified mesoporous carbon nanospheres B in a mass ratio of 7:3" to "modified mesoporous carbon nanospheres A and modified mesoporous carbon nanospheres B in a mass ratio of 1:9", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a core-ring confined structure aqueous zinc ion battery positive electrode material is obtained.

[0072] Comparative Example 3:

[0073] Step S1. Add 7 mL of deionized water, 40 mL of anhydrous ethanol, and 1 mL of aqueous ammonia into a beaker and stir evenly to obtain a mixture A; then add 0.6 g of ethyl orthosilicate, 0.4 g of resorcinol, and 0.7 g of formaldehyde solution into the mixture A in sequence and stir for 23 h to obtain a mixture B;

[0074] Step S2. The mixture B is centrifuged and washed, and the solid phase is obtained and then dried to obtain a compound C; the compound C is calcined at 650° C. for 26 h under a nitrogen atmosphere with a heating rate of 4° C. / min and etched with a 2 mol / L sodium hydroxide solution for 19 h in a 70° C. water bath to obtain a compound D;

[0075] Step S3. Centrifugally washing and drying the compound D to obtain hollow mesoporous carbon nanospheres;

[0076] Step S4. Dissolve 0.7g of ammonium metavanadate in 20mL of deionized water, add 3mL of ammonia water, and ultrasonically disperse to form a transparent solution E; ultrasonically disperse 1.5g of thioacetamide and 0.07g of hollow mesoporous carbon nanospheres with a diameter of 200-300nm and 600-800nm ​​in a mass ratio of 7:3 in solution E, and degas with a circulating water vacuum pump at a vacuum degree of -0.09MPa, and then transfer the black solution to a 50mL stainless steel high-pressure reactor; hydrothermally react at 175°C in a forced air drying oven for 11h, centrifuge and wash after the reaction, wash with deionized water and ethanol 6 times, and then vacuum dry at 60°C for 8 hours to obtain a core-ring confined structure aqueous zinc ion battery positive electrode material.

[0077] Performance Test:

[0078] Rate performance test:

[0079] The core-ring confined structure aqueous zinc ion battery positive electrode materials prepared in Examples 1-4 and Comparative Examples 1-3 were discharged at current densities of 0.1A / g, 0.5A / g, 1A / g, 2A / g, 4A / g, and 8A / g, and then returned to a current density of 0.1A / g for discharge, and the charge and discharge cycle was repeated for 10 cycles, and the discharge specific capacities were measured, respectively. The results are shown in Table 1.

[0080] Charge and discharge efficiency test:

[0081] The core-ring confined structure aqueous zinc ion battery positive electrode materials prepared in Examples 1-4 and Comparative Examples 1-3 were placed at a current density of 0.5 A / g for 30 weeks, and their charge and discharge efficiencies were measured. The results are shown in Table 1.

[0082] Cycle performance test:

[0083] The core-ring confined structure aqueous zinc ion battery positive electrode materials prepared in Examples 1-4 and Comparative Examples 1-3 were respectively placed under a current density of 0.5 A / g and cycled for 100 cycles, and their electrode capacities were measured. The results are shown in Table 1.

[0084] Table 1 Summary of experimental data in Examples 1-4 and Comparative Examples 1-3

[0085] project Discharge specific capacity / mol / (h·g) Charge and discharge efficiency / % Electrode capacity / mol / (h·g) Example 1 713.5 98 846.8 Example 2 698.9 96 824.9 Example 3 709.2 92 839.1 Example 4 692.6 95 825.6 Comparative Example 1 458.3 78 496.5 Comparative Example 2 528.4 83 633.8 Comparative Example 3 479.2 80 583.6

[0086] Data Analysis:

[0087] As can be seen from Table 1, the core-ring confined structure aqueous zinc ion battery positive electrode material prepared by the present invention has good rate performance, high charge and discharge efficiency, and stable cycle performance. This is because the present invention uses hollow mesoporous carbon nanospheres as nanoreactors, and synthesizes a novel structure of in-situ confined growth of core-ring structure vanadium disulfide inside hollow carbon spheres by vacuum degassing and hydrothermal methods. The three-dimensional nano hollow mesoporous carbon nanospheres show very high specific surface area and uniform porosity and good electrical conductivity, which is conducive to the rapid transportation of zinc ions and electrons; the porous carbon shell not only improves the conductivity of the composite material, but the porous structure on the carbon shell also provides a channel for the diffusion of zinc ions; in addition, the core-ring structure VS2 inside the carbon sphere can prevent the structure from falling off during the charge and discharge process, and the internal space can also buffer the volume effect during the zinc embedding / de-zincification process, which is conducive to the stability of the structure during the cycle.

[0088] However, in Comparative Example 1, 70% of modified mesoporous carbon nanospheres A are not added. It can be seen from Table 1 that the rate performance and cycle performance of its core-ring confined structure aqueous zinc ion battery positive electrode material are poor, and the charge and discharge efficiency is low. This is because mesopores of different diameters can more effectively disperse and load active components, improve loading efficiency and prevent aggregation of active components, and also form a more stable structure inside the material, reduce structural collapse during use, and improve the mechanical stability of the material. Therefore, the rate performance, charge and discharge efficiency and cycle performance shown in Comparative Example 1 are worse than those in Example 1; Comparative Example 2 adjusts "modified mesoporous carbon nanospheres A and modified mesoporous carbon nanospheres B with a mass ratio of 7:3" to "modified mesoporous carbon nanospheres A and modified mesoporous carbon nanospheres B with a mass ratio of 1:9". It can be seen from Table 1 that the rate performance and cycle performance of its core-ring confined structure aqueous zinc ion battery positive electrode material are poor, and the charge and discharge efficiency is low. This is because there are too few mesoporous carbon nanospheres with small diameters in the mesoporous carbon nanospheres used. These small-diameter mesoporous carbon nanospheres can provide a higher surface area, Thereby increasing the number of active sites or improving the adsorption capacity, and also providing a shorter ion diffusion path, thereby enhancing the conductivity of the electrode material, so the rate performance, charge-discharge efficiency and cycle performance exhibited by Comparative Example 2 are worse than those in Example 1; in Comparative Example 3, mesoporous carbon nanospheres with a diameter of 200-300nm and mesoporous carbon nanospheres with a diameter of 600-800nm ​​are directly reacted with thioacetamide at the same time to obtain a core-ring confined structure aqueous zinc ion battery positive electrode material. It can be seen from Table 1 that the rate performance and cycle performance of the core-ring confined structure aqueous zinc ion battery positive electrode material are poor, and the charge-discharge efficiency is low. This is because when the mesoporous carbon nanospheres with a diameter of 200-300nm and the mesoporous carbon nanospheres with a diameter of 600-800nm ​​are mixed and reacted with thioacetamide, the load will first enter the mesoporous carbon nanospheres with a large diameter, resulting in no load or less load in some mesoporous carbon nanospheres with a small diameter, thereby affecting the conductivity of the electrode material. Therefore, the rate performance, charge-discharge efficiency and cycle performance exhibited by Comparative Example 3 are worse than those in Example 1.

[0089] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0090] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a core-ring confined structure aqueous zinc ion battery positive electrode material, characterized in that: The following steps are involved: Step S1. Add deionized water, anhydrous ethanol and ammonia water into a beaker and stir evenly to obtain a mixture A; then add ethyl orthosilicate, resorcinol and formaldehyde solution into the mixture A in sequence and stir to obtain a mixture B; Step S2. Wash the mixture B by centrifugation, obtain the solid phase and dry it to obtain compound C; calcine compound C at high temperature under nitrogen atmosphere protection, and etch it with a strong alkaline solution in a water bath to obtain compound D; Step S3. Centrifugally washing and drying the compound D to obtain hollow mesoporous carbon nanospheres; Step S4. dissolving ammonium metavanadate in deionized water, adding ammonia water, and ultrasonically forming a transparent solution E; ultrasonically dispersing thioacetamide and hollow mesoporous carbon nanospheres in solution E, degassing under vacuum conditions, hydrothermal reaction, centrifugal washing, obtaining a solid phase, and vacuum drying to obtain modified mesoporous carbon nanospheres A; Step S5. dissolving ammonium metavanadate in deionized water, adding ammonia water, and ultrasonically forming a transparent solution E; ultrasonically dispersing thioacetamide and hollow mesoporous carbon nanospheres in solution E, degassing under vacuum conditions, hydrothermal reaction, centrifugal washing, obtaining a solid phase, and vacuum drying to obtain modified mesoporous carbon nanospheres B; Step S6. Mixing the modified mesoporous carbon nanosphere A and the modified mesoporous carbon nanosphere B to obtain a core-ring confined structure aqueous zinc ion battery positive electrode material; The diameter of the hollow mesoporous carbon nanospheres in step S4 is 200-300 nm; The diameter of the hollow mesoporous carbon nanospheres in step S5 is 600-800 nm; The mass ratio of the modified mesoporous carbon nanospheres A to the modified mesoporous carbon nanospheres B in step S6 is 7:

3.

2. The method for preparing the core-ring confined structure aqueous zinc ion battery positive electrode material according to claim 1, characterized in that: The volume ratio of deionized water, anhydrous ethanol and ammonia water in step S1 is 3-8:23-47:

1.

3. The method for preparing the core-ring confined structure aqueous zinc ion battery positive electrode material according to claim 1, characterized in that: The mass fraction of the ammonia water in step S1 is 25%.

4. The method for preparing the core-ring confined structure aqueous zinc ion battery positive electrode material according to claim 1, characterized in that: In step S1, the mass ratio of ethyl orthosilicate, resorcinol and formaldehyde is 0.2-0.8:0.1-0.5:0.1-1, and the stirring time is 20-24 hours.

5. The method for preparing the core-ring confined structure aqueous zinc ion battery positive electrode material according to claim 1, characterized in that: The high temperature calcination temperature in step S2 is 500-700°C, the heating rate is 1-5°C / min, and the water bath temperature is 70°C.

6. The method for preparing the core-ring confined structure aqueous zinc ion battery positive electrode material according to claim 1, characterized in that: The strong alkali solution in step S2 is any one of sodium hydroxide and potassium hydroxide, and the concentration of the strong alkali solution is 1-3 mol / L.

7. The method for preparing the core-ring confined structure aqueous zinc ion battery positive electrode material according to claim 1, characterized in that: In step S2, the etching temperature is 70° C., and the etching time is 16-20 hours.

8. The method for preparing the core-ring confined structure aqueous zinc ion battery positive electrode material according to claim 1, characterized in that: The hollow mesoporous carbon nanospheres in step S3 have a carbon wall thickness of 8-10 nm and a mesopore size of 1-5 nm.

9. The method for preparing the core-ring confined structure aqueous zinc ion battery positive electrode material according to claim 1, characterized in that: In step S4, the mass ratio of ammonium metavanadate, thioacetamide and hollow mesoporous carbon nanospheres is 0.3-0.8:0.3-2:0.03-0.1, and the volume ratio of ammonia water to deionized water is 1-4:10-30; In step S5, the mass ratio of ammonium metavanadate, thioacetamide and hollow mesoporous carbon nanospheres is 0.3-0.8:0.3-2:0.03-0.1, and the volume ratio of ammonia water to deionized water is 1-4:10-30.

10. The method for preparing the core-ring confined structure aqueous zinc ion battery positive electrode material according to claim 1, characterized in that: The vacuum degassing equipment in step S4 is a circulating water vacuum pump with a vacuum degree of -0.1--0.07MPa; The hydrothermal reaction temperature in step S4 is 100-200° C., and the reaction time is 8-12 h.

Citation Information

Patent Citations

  • Three-dimensional porous graphene-vanadium disulfide composite electrode material, and preparation method and application thereof

    CN108597908A

  • Defect-rich vanadium disulfide, preparation method thereof and application of defect-rich vanadium disulfide as positive electrode material in aqueous zinc ion battery

    CN115092960A

Cited By

  • VS4 / C composite material as well as preparation method and application thereof

    CN120784332A

  • A VS4 / C composite material, its preparation method and application

    CN120784332B